Seven New Species of Crayfish of the Genus Cherax (Crustacea, Decapoda, Parastacidae) from Western New Guinea, Indonesia - Christian Lukhaup; Rury Eprilurahman; Thomas von Rintelen (Arthropoda)
Seven new species of the genus Cherax from the western region of Western New Guinea, Indonesia, are described and illustrated. All new species—Cherax veritas n. sp. from the southeastern part of Misool Island of Raja Ampat Regency, Southwest Papua; Cherax arguni n. sp. and Cherax kaimana n. sp. from the northern part of Kaimana Regency, West Papua; Cherax nigli n. sp. from the southeastern part of Kaimana Regency, West Papua; Cherax bomberai n. sp. from the northeastern part of the Fakfak Regency, West Papua; Cherax farhadii n. sp. and Cherax doberai n. sp. from the Teluk Bintuni Regency, West Papua—belong to the northern group of Cherax. The new species are compared with their closest relatives, from which they can all be easily distinguished by morphological characters, such as the shape of the chelae, rostrum, body, and by their coloration. A molecular phylogeny based on a mitochondrial gene fragment, 16S, supports the morphology-based description of the seven new species, which can also be clearly distinguished by sequence differences.